2022
DOI: 10.1021/acsnano.2c09527
|View full text |Cite
|
Sign up to set email alerts
|

Edge and Interface Resistances Create Distinct Trade-Offs When Optimizing the Microstructure of Printed van der Waals Thin-Film Transistors

Abstract: Inks based on two-dimensional (2D) materials could be used to tune the properties of printed electronics while maintaining compatibility with scalable manufacturing processes. However, a very wide range of performances have been reported in printed thin-film transistors in which the 2D channel material exhibits considerable variation in microstructure. The lack of quantitative physics-based relationships between film microstructure and transistor performance limits the codesign of exfoliation, sorting, and pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Importantly, the printed high-density transistor arrays (∼47 000 transistors·cm –2 ) deliver an average mobility of ∼4.2 cm 2 ·V –1 ·s –1 and an on/off ratio of ∼10 6 , representing the highest device density to date in the printed TMD materials (Figure c). Zhu et al found that the presence of fixed negative charges at nanosheet edges could induce a large local increase in resistance that limits effective mobility . Hence, passivating the edges of nanosheets may be an effective method to further improve the mobility of the printed vdW films.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, the printed high-density transistor arrays (∼47 000 transistors·cm –2 ) deliver an average mobility of ∼4.2 cm 2 ·V –1 ·s –1 and an on/off ratio of ∼10 6 , representing the highest device density to date in the printed TMD materials (Figure c). Zhu et al found that the presence of fixed negative charges at nanosheet edges could induce a large local increase in resistance that limits effective mobility . Hence, passivating the edges of nanosheets may be an effective method to further improve the mobility of the printed vdW films.…”
Section: Applicationsmentioning
confidence: 99%
“…Zhu et al found that the presence of fixed negative charges at nanosheet edges could induce a large local increase in resistance that limits effective mobility. 319 Hence, passivating the edges of nanosheets may be an effective method to further improve the mobility of the printed vdW films.…”
Section: Field-effect Transistors and Logic Devicesmentioning
confidence: 99%
“…Previous investigations have shown that deposited MoS 2 layers (from bulk flakes) formed from a drop-cast suspension showed very limited electrical conductivity between the interflakes of the MoS 2 [16]. This degraded charge transport may be due to carrier depletion and scattering at the edge of these overlapping MoS 2 flakes [17]. Spin-coated hybrid films from MoS 2 suspension in a polymeric semiconductor have been reported where the suspension was found to improve the transport properties of the TFT devices [11][12][13]18], but it is still unclear whether the suspension only affects the electrical characteristics through changes to the electronic structure.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, two-dimensional layered materials (2DLMs) have gained significant attention as alternative candidates for preparing colloidal inks, offering several potentials in the fabrication of solution-processed TFTs. These atomically thin materials, consisting of van der Waals ( vdW ) bonded atomic layers, exhibit a diverse range of electronic properties, including semimetallic graphene, semiconducting transition metal dichalcogenides (TMDCs), and insulating hexagonal boron nitride ( h -BN). , The 2D layered structure allows for precise control over their thickness and uniformity in film formation, enabling the fabrication of ultrathin devices with distinct properties and functionalities. Additionally, 2DLMs exfoliated (electro)­chemically in solution exhibit stability and processability. They can be effectively dispersed in solvents to form inks or suspensions, allowing for solution-based deposition techniques such as spin coating, inkjet printing, and spray coating .…”
mentioning
confidence: 99%